Training of non-radiologist medical doctors in ultrasound in Ghana - Jumali, K.B.; Brakohiapa, W.O.; Obajinii, M.G.; Armah, J.O.; Seffah, J.D.; Kragt, J. (Ghana Medical Journal, 2001)
Ultrasound is an important diagnostic equipment widely used in modem medical practices. Appropriate high-quality ultrasound services are best provided by properly trained and committed radiologists and sonographers, using high-quality ultrasound equipment. In terms of use of both manpower and equipment, the Department of Radiology ultrasound service offers the best value for money. An ultrasound service sited within the Department of Radiology allows patients to be given the benefit of the radiologist's ability to use alternative or additional imaging techniques to deal with the clinical problem without delay. Outreach services, staffed by sonographers or radiologist arc likely to provide the most cost-effective use of skilled manpower in providing a wider, more accessible ultrasound service for patients where appropriate. Notwithstanding the points made above, there is the need 10 extend ultrasound services outside the main teaching and regional hospitals to the district hospitals and the polyclinics. Hence the need to train non-radiologist to these centers and to provide ultrasound equipment for these centers. Unfortunately, there have been acquisition of all types of ultrasound equipment by private individuals and clinics in the country which is being operated by doctors with very little or no technical know-how and issuing ultrasound medical reports
Journal Article
Keywords: Ultrasound; radiologists; sonographers; Medical Systems; Ghana